2015
DOI: 10.1055/s-0041-108199
|View full text |Cite
|
Sign up to set email alerts
|

Development and Suggestion of a Cardiac CTA Scoring System for the Prediction of Revascularization Success in Chronic Total Occlusions (CTO) of the Coronary Arteries

Abstract: Heart 172Roller FC et al. Development Objective: Analyzing occluded segments with computed tomography angiography (CTA) prior to percutaneous coronary intervention (PCI) increased revascularization success in chronic total occlusions (CTO). The aim of our study was to develop a scoring system for the prediction of PCI success in CTO. Materials and Methods: 41 consecutive CTO patients (30 male; 63.1 years +/-8.3 standard deviation) underwent CTA prior to PCI. All CTOs were categorized by two radiologists in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…KCCT prediction model displayed excellent discriminatory power for guidewire crossing in 30 min (AUC 0.776 vs. 0.703, respectively) and final procedural success (AUC 0.773 vs. 0.717, respectively), which was consistent in both studies. Roller et al [36] proposed a new five-item CT-based score with good prediction power (AUC 0.8232). Nonetheless, a small cohort of patients was included, and results should be confirmed in more extensive studies.…”
Section: Resultsmentioning
confidence: 99%
“…KCCT prediction model displayed excellent discriminatory power for guidewire crossing in 30 min (AUC 0.776 vs. 0.703, respectively) and final procedural success (AUC 0.773 vs. 0.717, respectively), which was consistent in both studies. Roller et al [36] proposed a new five-item CT-based score with good prediction power (AUC 0.8232). Nonetheless, a small cohort of patients was included, and results should be confirmed in more extensive studies.…”
Section: Resultsmentioning
confidence: 99%
“…28 Other CT-derived parameters which can predict the success of a CTO-PCI include the degree and distribution of coronary calcification, degree of coronary tortuosity, distal coronary vessel size and proximal cap morphology. 27,[29][30][31][32][33][34] Scores based on preprocedural CTA have also been developed, such as CT-RECTOR and KCCT. 35,36 CT-RECTOR showed that the preprocedural CTAbased model had superior performance compared with the J-CTO angiography-based score.…”
Section: Collateral Vesselsmentioning
confidence: 99%
“…Several studies aimed at developing success prediction models have been carried out and the use of classical risk factors including, the length of the occlusion (>20 mm), blunt stump, CTO calcification, CTO tortuosity, and prior failed attempt, have shown good discriminatory capacity on the success of antegrade CTO PCI. There are still some noticeable limitations to CTO‐PCI intervention especially regarding the hybrid approach and retrograde recanalization .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies aimed at developing success prediction models have been carried out [10][11][12] and the use of classical risk factors 13 including, the length of the occlusion (>20 mm), blunt stump, CTO calcification, CTO tortuosity, and prior failed attempt, have shown good discriminatory capacity on the success of antegrade CTO PCI.…”
mentioning
confidence: 99%